Andrographis paniculata: a review of pharmacology and clinical efficacy - Sangita Boro; Manisha Chirania; Deepjyoti Boro; Bhriganka Bharadwaj; Mitali Baruah; Minakshi Bhattacharjee (Faculty of Medicine, Universitas Trisakti, 2026)
Andrographis paniculata is widely regarded as one of the most important medicinal plants due to its broad therapeutic value and global use in traditional medicine. Commonly known as Kalmegh, creat, or green chirayata, the plant has been an integral part of Ayurvedic, Siddha, Unani, and other traditional healing systems for centuries. It has traditionally been consumed to manage a variety of ailments, particularly those related to the liver, respiratory system, and immune health. Phytochemical investigations have revealed that Andrographis paniculata is rich in diverse bioactive constituents. Among these, andrographolide, neoandrographolide, and didehydroandrographolide are the most prominent diterpenoid lactones. Andrographolide, in particular, is recognized as the principal active compound and has been extensively studied for its wide pharmacological spectrum. Research indicates that andrographolide exhibits strong hepatoprotective, antioxidant, anti-inflammatory, immunomodulatory, antibacterial, antipyretic, anti-diabetic, and anti-cancer activities. These properties contribute to the plant’s reputation as a versatile therapeutic agent. In this review, we systematically searched and analyzed articles published in English from 2019 to 2025, using PubMed, ScienceDirect, Springer Link, and Google Scholar. Relevant search terms included “Andrographis paniculata”, pharmacology”, “clinical efficacy”, “safety”, etc. Given its chemical richness and diverse pharmacological actions, Andrographis paniculata continues to attract scientific attention. Numerous studies support its potential in managing chronic diseases, enhancing immune function, and mitigating oxidative stress. This review aims to provide a concise yet comprehensive overview of the plant’s therapeutic relevance, highlighting its major chemical constituents and summarizing key findings from pharmacological evaluations and clinical safety and efficacy reported in the scientific literature. By synthesizing existing knowledge, this review emphasises the significance of Andrographis paniculata as a promising natural resource in herbal medicine and modern pharmacotherapy.